2023
DOI: 10.3390/dj11050131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Third Molars on the Mandibular Anterior Crowding Relapse—A Systematic Review

Abstract: The present systematic review updates the evidence on wisdom teeth contributing to lower incisor crowding following orthodontic treatment. Relevant literature was searched on online databases, namely Pubmed, Scopus, and Web of Science, up to December 2022. Eligibility criteria were formulated using the PICOS approach and PRISMA guidelines. Eligible research included original clinical studies involving patients previously being treated orthodontically with permanent dentition at the end of treatment, regardless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…shows that orthodontists do not consider third molar eruption as a cause of early relapse after treatment ( 16 ). In general, clinical studies have reinforced this position by demonstrating that relapse can occur regardless of the presence or absence of third molars ( 6 , 26 ). However, it has also been proposed that interproximal force may increase due to late eruption of the third molars, which would generate some movement in lower incisors, requiring constant evaluation after completing the retention phase ( 7 , 28 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…shows that orthodontists do not consider third molar eruption as a cause of early relapse after treatment ( 16 ). In general, clinical studies have reinforced this position by demonstrating that relapse can occur regardless of the presence or absence of third molars ( 6 , 26 ). However, it has also been proposed that interproximal force may increase due to late eruption of the third molars, which would generate some movement in lower incisors, requiring constant evaluation after completing the retention phase ( 7 , 28 ).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, there is longitudinal evidence to affirm that mandibular crowding is not influenced by the third molars ( 25 ). Although the literature is not conclusive in this regard, it has been stated that lower anterior crowding over the years may be due to other factors such as the tensile forces of the neighboring soft tissues, dimensions of the teeth, condition periodontal, evolutionary factors, sex and race of the patient ( 26 ). However, it should be considered that the responses in the present study were from orthodontic specialists and general practice dentists, compared to previous studies where only specialists participated.…”
Section: Discussionmentioning
confidence: 99%
“…Some orthodontists and oral surgeons recommend extracting third molars to prevent the crowding of teeth upon their eruption [30]. However, recent studies do not present sufficient evidence to advocate the preventive removal of wisdom teeth to obtain occlusal stability [31,32]. The study of Dosumu et al showed poor knowledge of the consequences of missing teeth among patients with partial edentulism [28].…”
Section: Missing Teethmentioning
confidence: 99%
“…[42] Implants were often inserted around tooth FDI 26/UNS 14 (6 times). In the study group, implants were not placed in the place of teeth FDI 18,17,28,38,37,[34][35][36][37][38][39][40][41][42][43][44]47,48/UNS 1,2,16,17,18,[21][22][23][24][25][26][27][28]31,32. According to a report concerning trends in dental implants in the US in 1999-2016, most were placed in posterior sites, almost equally in the maxilla and mandible [43]. The anterior maxillary region, being an aesthetic zone, requires special attention in the treatment plan to eliminate the risk of positioning errors, considering gingival phenotype, the width of the edentulous space, and bone anatomy at the alveolar crest [44].…”
Section: Restoring Missing Teeth With Dental Implants and Bridgesmentioning
confidence: 99%
“…The primary reason for the retention of M3s is a deficit of space in the dental arch, resulting from evolutionary changes in the reduction in the bone base of the maxilla and mandible [ 8 ]. Less common causes of third molar impaction (I-M3) are incorrect positioning of the tooth bud, intraosseous pathologies, such as cysts or odontogenic tumors, or genetic diseases, such as cleidocranial dysplasia and ectodermal dysplasia [ 9 , 10 ]. The high incidence of third molar impaction makes the management of third molars an important role in public health.…”
Section: Introductionmentioning
confidence: 99%